Milestones in Microwave Chemistry - Keglevich, György (SpringerBriefs in Green Chemistry for Sustainability, 2016)
This book looks back on thirty-five years of microwave (MW) chemistry and explains how the application of the MW technique became an integral part of R&D, eventually becoming recognized in industry. Further, it details how MW chemistry has undergone a dynamic development in the past three decades, one driven by the advent of increasingly sophisticated professional MW reactors in place of the kitchen MW ovens used in earlier years. A major part of the book shows how substitutions, esterifications, amidations, hydrolyses, alkylations, eliminations, dehydrations, condensations, cyclizations, C-C couplings and the modification of heterocycles can be performed advantageously under MW irradiation, as the reaction times are shorter, while the selectivity and yields are higher; it also explains why in most cases, the reactions can be performed under solvent-free conditions. MW irradiation within the sphere of organophosphorus chemistry is showcased and typical reactions, such as the direct derivatization of phosphinic acids, alkylating esterifications, Diels-Alder reactions, the inverse Wittig-type reaction, fragmentations, the Arbuzov reaction, the synthesis of α-hydroxyphosphonates and α-aminophosphonates (the Kabachnik-Fields condensation), deoxygenations and P-C coupling reactions are described under MW conditions. In closing, the advantages of MW chemistry such as faster reactions and the possibility of simplifying the catalytic systems are addressed.